Polymer Biointerfaces - Lehocký, Marián; Humpolíček, Petr (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Dear Colleagues, Polymer biointerfaces are considered a suitable alternative to the improvement and development of numerous applications. The optimization of polymer surface properties can control several biological processes, such as cell adhesion, proliferation, viability, and enhanced extracellular matrix secretion functions at biointerfaces. This printed Special Issue on Polymer Biointerfaces is focused on fundamental and applied research on polymers and systems with biological origin. Submissions contain both polymer material background and descriptions of interacting biological phenomena or relevance to prospective applications in biomedical, biochemical, biophysical, biotechnological, food, pharmaceutical, or cosmetic fields. Special attention has been given to polymer bio-surface modification, bio-coatings, cell-polymer surface interactions, self-assembling monolayers on polymers, in-vivo and in-vitro systems, protein-polymer surface interaction, polysaccharide-polymer interactions, biotribology, bio chip, biosensors, nano-bio interfaces, coatings, biofilms, adhesion phenomena, and molecular recognition, among others. Assoc. Prof. Marián LehockýAssoc. Prof. Petr HumpolíčekGuest Editors